Establishment of a stable transfection and gene targeting system in Babesia divergens - Cubillos, Eliana F. G.; Snebergerova, Pavla; Borsodi, Sarka; Reichensdorferova, Dominika; Levytska, Viktoriya; Asada, Masahito; Sojka, Daniel; Jalovecka, Marie (Frontiers in Cellular and Infection Microbiology, 2023)
Babesia divergens is an emerging tick-borne pathogen considered as the principal causative agent of bovine babesiosis in Europe with a notable zoonotic risk to human health. Despite its increasing impact, considerable gaps persist in our understanding of the molecular interactions between this parasite and its hosts. In this study, we address the current limitation of functional genomic tools in B. divergens and introduce a stable transfection system specific to this parasite. We define the parameters for a drug selection system hdhfr-WR99210 and evaluate different transfection protocols for highly efficient generation of transgenic parasites expressing GFP. We proved that plasmid delivery into bovine erythrocytes prior to their infection is the most optimal transfection approach for B. divergens, providing novel evidence of Babesia parasites' ability to spontaneously uptake external DNA from erythrocytes cytoplasm. Furthermore, we validated the bidirectional and symmetrical activity of ef-tgtp promoter, enabling simultaneous expression of external genes. Lastly, we generated a B. divergens knockout line by targeting a 6-cys-e gene locus. The observed dispensability of this gene in intraerythrocytic parasite development makes it a suitable recipient locus for further transgenic application. The platform for genetic manipulations presented herein serves as the initial step towards developing advanced functional genomic tools enabling the discovery of B. divergens molecules involved in host-vector-pathogen interactions.